The Potential for Heat Treating Cemented Carbides - Kříž, Antonín; Bricín, David; Průcha, Vojtěch (Manufacturing Technology Journal, 2018)
The focus at the outset was on nothing more than cryogenic treatment of cemented carbides. Then, in relation to additional findings arising from heating of cemented carbides, this paper was expanded to include the results of heat treatment and the behaviour at elevated temperatures. Although heat treatment is applied to diverse materials, no profound study of heat treatment has been dedicated to cemented carbides. This is despite the fact that both cryogenic treatment and heating to elevated temperatures have been proven to cause changes in their properties. Not all these changes are favourable. If precisely-defined rules are not followed, the changes may be adverse. The interest in heat treatment of cemented carbide has been very low. This paper not only provides comprehensive information on the properties of heat-treated cemented carbides but also presents the processes which take place in cemented carbides under load.
Keywords: Cemented Carbides; WC-Co; Heat Treatment; Cryogenic Treatment; Wear